2021
DOI: 10.1136/bmjopen-2020-044831
|View full text |Cite
|
Sign up to set email alerts
|

Direct and mediated effects of treatment context on low back pain outcome: a prospective cohort study

Abstract: ObjectivesContextual components of treatment previously associated with patient outcomes include the environment, therapeutic relationship and expectancies. Questions remain about which components are most important, how they influence outcomes and comparative effects across treatment approaches. We aimed to identify significant and strong contextual predictors of patient outcomes, test for psychological mediators and compare effects across three treatment approaches.DesignProspective cohort study with patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 77 publications
(90 reference statements)
0
33
0
Order By: Relevance
“…The context in which clinicians deliver healthcare interventions can improve or reduce the overall effect of an intervention. Like other non-pharmacological interventions, factors such as the patient-practitioner relationship and patients’ expectations could impact acupuncture’s effectiveness 28…”
Section: Trials Often Overlook Contextual Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The context in which clinicians deliver healthcare interventions can improve or reduce the overall effect of an intervention. Like other non-pharmacological interventions, factors such as the patient-practitioner relationship and patients’ expectations could impact acupuncture’s effectiveness 28…”
Section: Trials Often Overlook Contextual Effectsmentioning
confidence: 99%
“…Like other non-pharmacological interventions, factors such as the patient-practitioner relationship and patients’ expectations could impact acupuncture’s effectiveness. 28 …”
Section: Trials Often Overlook Contextual Effectsmentioning
confidence: 99%
“…A recent study found that statistically significant predictors of reduced back-related disability were; a stronger therapeutic alliance, higher patient satisfaction, reduced patient-perceived treatment credibility, and increased practitioner-rated outcome expectancies. Stronger therapeutic alliance demonstrated the largest effect sizes [29]. Other studies [30] have also shown that therapeutic alliance modulates pain in experimental settings using physical therapy and in encounters where spinal manipulative therapy is provided [31].…”
Section: Professional Identitymentioning
confidence: 94%
“…WA incorporates cognitive and emotional dimensions of the interpersonal processes between both parties occurring during care [4]. Research has demonstrated that WA is associated with physical function, pain, disability, patient satisfaction, adherence to the treatment plan and overall perceived effect of treatment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it could be argued that strong WA can provide the foundational environment necessary for patients to benefit from the effects of contextual factors present in all chiropractic consultations [17] by eliciting psychological and/or behavioural changes [18]. For example, a large prospective cohort study illustrated that WA decreased disability at least partly by improving patients' self-efficacy for coping and reducing psychosocial distress and the perceived threat of low back pain [5]. A more comprehensive understanding of WA will enable chiropractors to learn how to skilfully use contextual factors which in turn can drive modulation of pain [15].…”
Section: Introductionmentioning
confidence: 99%